Prostaglandins Isolated from the Octocoral Plexaura homomalla: In Silico and In Vitro Studies Against Different Enzymes of Cancer - Diana Ximena Hurtado; Fabio A. Castellanos; Ericsson Coy-Barrera; Edisson Tello (Marine Drugs, 2020)
Prostaglandin A2-AcMe (1) and Prostaglandin A2 (2) were isolated from the octocoral Plexaura homomalla and three semisynthetic derivatives (3−5) were then obtained using a reduction protocol. All compounds were identified through one- and two-dimensional (1D and 2D) nuclear magnetic resonance (NMR) experiments. Additionally, evaluation of in vitro cytotoxic activity against the breast (MDA-MB-213) and lung (A549) cancer cell lines, in combination with enzymatic activity and molecular docking studies with the enzymes p38α-kinase, Src-kinase, and topoisomerase IIα, were carried out for compounds 1−5 in order to explore their potential as inhibitors of cancer-related molecular targets. Results showed that prostaglandin A2 (2) was the most potent compound with an IC50 of 16.46 and 25.20 μg/mL against MDA-MB-213 and A549 cell lines, respectively. In addition, this compound also inhibited p38α-kinase in 49% and Src-kinase in 59% at 2.5 μM, whereas topoisomerase IIα was inhibited in 64% at 10 μM. Enzymatic activity was found to be consistent with molecular docking simulations, since compound 2 also showed the lowest docking scores against the topoisomerase IIα and Src-kinase (−8.7 and −8.9 kcal/mol, respectively). Thus, molecular docking led to establish some insights into the predicted binding modes. Results suggest that prostaglandin 2 can be considered as a potential lead for development inhibitors against some enzymes present in cancer processes.